Development of a core set of clinical care provision indicators for non-specialist palliative care in hospitals - NEVIN, MARY (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2020)
Background: Ageing populations with associated chronic illnesses and multi-morbidity will lead to a rapidly escalating need for all levels of palliative care provision. This will place significant pressures on health systems to optimise the utilisation of all resources, including hospital-based care. For most patients presenting to hospital with palliative care needs, these needs can be met by healthcare providers who do not work within specialist palliative care services. However, integrating non-specialist palliative care (NSPC) within acute care delivery in hospitals is challenging and requires multi-level organisational support. Therefore, this study seeks to explore NSPC, to understand the issues associated with the delivery of NSPC in hospitals, and to use the knowledge gained to develop core clinical care provision indicators for NSPC in hospitals. These can provide a basis to support multi-level integration of NSPC in the hospital care setting. Aim: To develop a core set of clinical care provision indicators (CCPIs) for non-specialist palliative care in hospitals. Methods: This study had three distinct, yet complimentary phases; - Phase I: A principle-based concept analysis; to analyse terminology associated with this care, how the concept of NSPC is currently understood, and key attributes of NSPC from multiple philosophical perspectives; - Phase II: A qualitative systematic review; to explore the experiences, barriers and facilitators of NSPC from the views of healthcare providers engaged in NSPC provision in hospitals to understand relevant contextual issues for the provision of NSPC in hospitals; - Phase III: A Delphi study to identify, through International consensus, core CCPIs for NSPC in hospitals, and to make recommendations for future policy, practice, research and education. Findings: A total of 124 papers were included in the concept analysis of NSPC. Findings from this phase uncovered diverse meanings and definitions employed to describe NSPC reflecting the ambiguous nature of the concept. Attributes of NSPC were identified with various degrees of operationalization/abstractness but were generally poorly measured and understood in practice. NSPC was found to be strongly associated with quality of life, holism and patient-centred care. While there was some consistency in meaning across healthcare disciplines, there was blurring of boundaries particularly with specialist palliative care and a lack of clear roles and boundaries within NSPC provision. Phase II included a total of thirty-nine papers (reporting on thirty-seven studies). Thematic synthesis produced four dominant themes relating to inadequate knowledge and competency in NSPC, poor communication between healthcare providers, and with patients, particularly in relation to worsening prognosis, differing perspectives of nurses and doctors relating to their perceived role in NSPC provision, and several environment issues that impacted on providers ability to provide adequate NSPC. The findings from phases I and II were used to inform an initial list of 34 CCPIs which were presented to participants in round one of the Delphi study (phase III). A further 12 indicators, based on participants' suggestions, were added following round 1. A total of seventy-two of 97 experts (e.g. healthcare providers, patients, researchers) from twelve countries participated in the final Delphi round (74% overall response rate). Consensus was achieved on 32 core CCPIs for hospital-based NSPC with: five structural indicators (relating to infrastructure and governance), 21 organisational indicators (relating to clinical care processes) and six staff indicators (relating to training and support for healthcare providers). Discussion and Conclusion: This study presents an advancement of the conceptual basis of NSPC and a greater understanding of the contextual issues associated with NSPC practice in hospitals. The core set of 32 CCPIs for NSPC in hospitals developed in this study reflect the fundamental palliative perspective of total pain and whole person care, highlighting the importance of a multidisciplinary approach for the provision of NSPC in hospitals, the interface between NSPC and specialist palliative care, and the essential training needs for NSPC providers. These core CCPIs incorporate multi-level guidance for clinical practice, policy and research for NSPC in hospitals. They provide a means to assess, review, and communicate the essential elements required to integrate NSPC within hospitals, thereby setting a benchmark for informing policy and practice.
APPROVED
Keywords: Palliative care; Acute Hospital